DS 95: Proceedings of the 21st International Conference on Engineering and Product Design Education (E&PDE 2019), Universit 2019
DOI: 10.35199/epde2019.73
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Challenges of Global Collaboration Through Design Education

Abstract: The challenges of integrating technology in global design classes have been published in the literature, but it is unclear if this knowledge makes its way back to the classroom. This paper investigates knowledge transfer by documenting the results of four workshops across two institutions and two distributed design classes. Participants were asked to identify the challenges of distributed design, the functionality of technologies to overcome the challenges and guidance on how best to perform distributed design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Even though researchers reported that students use various ICT tools in a distributed product based PBL courses, many challenges to their effective use still exist. Students can overcome some challenges using video conferencing, instant messaging and collaborative document editing tools (Brisco et al, 2019). However, learning new ICT tools might require a significant amount of time.…”
Section: Use Of Ict Tools In Product Design Pbl Coursesmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though researchers reported that students use various ICT tools in a distributed product based PBL courses, many challenges to their effective use still exist. Students can overcome some challenges using video conferencing, instant messaging and collaborative document editing tools (Brisco et al, 2019). However, learning new ICT tools might require a significant amount of time.…”
Section: Use Of Ict Tools In Product Design Pbl Coursesmentioning
confidence: 99%
“…Students reported that they were more familiar with the tools they have chosen themselves and did not have time to learn another ICT tool given the course's high pace. Therefore, previous experience is one of the main forces that drive a decision on choosing another ICT tool (Brisco et al, 2019). Hence, students might feel that learning additional CAD tools is time-consuming and presents a distraction -a common reason for not adopting a suggested ICT tool (Verstegen et al, 2016).…”
Section: Previous Experience and Adopting Suggested Ict Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some include specific templates for designers including decision making frameworks or ideation brainwriting. There are many case studies reported in the literature of distributed design teams conducting design activities as online technology capabilities grow, including synchronous CAD [2], social network sites [3], collaborative document editors [4], learning management systems [5], and video conference [6] for a range of design activities including design review meetings, democratic decision making (voting/polling), annotating concepts, CAD development and a range of design methods including TRIZ, design alternatives, market research and feedback from stakeholders. Over time, there have been novel developments of design methods and tools which are inspired by computer functionality.…”
Section: Introductionmentioning
confidence: 99%